The Da'i (Muslim Preachers) and Social Change Challenges: a Study of Da'i Professionalism in Dumai, Riau - Toni Hartono; Masduki Masduki; Pipir Romadi (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2020)
This article examines the preacher's professionalism in the dynamics of social change in the Dumai Muballigh (Muslim Preacher)Association (PMD). The development of information technology is one of the causes of social changes that occur and currently shows the complexity of the problems faced by the people and preachers. Da'wah as a call, invitation, and appeal is expected to be transformed to be relevant to any changes that occur. This requires professional preachers to be able to become agents of change. In preaching, the development of preaching resources is emphasized on various aspects such as material, mental, skills, knowledge, and psychic. The results showed that the effort to create professional preachers in the PMD is doing human resource development through muzakarah and preaching guidance to strengthen science and skills, training and use of IT (Information Technology) as a form of transformation, conducting preaching certification as an effort to assess and qualify the quality of preachers' abilities, improving education levels through further education cooperation agreements among preachers and companies, universities and government, and the development of contemporary preaching material through the study of books, and hadith.